Estimation of efficiency of mastering of the program on discipline «Physical education» of pedagogical specialities students. - Tsymbalyuk Z.A; Chorniy A.I; Kos'yan А.V; Shevtsov A.A (Kharkov National Pedagogical University, 2012)
Purpose of work − to define the diagnostic model of quantitative estimation of jurisdictions of students in relation to the decision of problems in the field of physical education. The students of I-IV of courses took part in an experiment. The qualimetry method of estimation was utillized. The on-line and working tutorial of discipline is developed on module principle. The table of extra charge of marks of results of estimation of physical preparedness of students is recommended. It is set that efficiency of mastering of the program on discipline it is possible to estimate «Physical education» by criteria. The first criterion is a level of development of physical qualities and formed of motive skills; second is a level of the special theoretical knowledge; third is a level organizationally methodical abilities; fourth is a level of readiness of the functional systems; fifth is the personal responsibility for the state of health.